Museum as creativity: building the universal through the individual - Babić, Darko muzeolog (Array, 2011)
The paper is based upon a recently opened museum in Zagreb, the Museum of Broken Relationships whose concept raises questions about the conventional ways of meaning making in museums in general and scientific (curatorial) approach to material culture. This museum represents a new sort of cultural institution which focuses on the idea of the universal through individual contribution to meaning making. Positioning the concept of this museum in a wider museological framework the paper offers a potential redefinition of the nature and the role of museums and their use of artefacts in communicating with audiences. First conceived as a travelling event, and receiving its permanent display only six months ago, the Museum of Broken Relationships is formed by artefacts which represent former relationships. Each artefact, mainly a mass product, is donated by people who also write their own explanation of the artefacts they donated. The authenticity of each artefact is in that way created by a personal story. In other words, instead of being formed by institutional authority figures (curators) interpretations for the artefacts are produced by "laymen" - both those who donated the artefacts and visitor who identify themselves with these stories and objects in an act similar to reading a literary work. The paper therefore aims to explore distinctive features of artefacts as composite museum objects and “private signs”, and relate them to a possible altering of the structure of the museum language and a different approach to material culture which is not strictly understood as a social practice, but private-public ritual of exchanging experiences and emotions. These processes of accepting and displaying individual narratives about artefacts might lead to the formation of another sort of museum taxonomy which would come very close to what is known as folksonomy.